1996
DOI: 10.1007/bf00240038
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of and intervention into the oxidative pentose phosphate pathway and adenine nucleotide metabolism in the heart

Abstract: The capacity of the oxidative pentose pathway (PPP) in the heart is limited, since the activity of glucose-6-phosphate dehydrogenase (G-6-PD), the first and regulating enzyme of this pathway, is very low. Two mechanisms are involved in the regulation of this pathway. Under normal conditions, G-6-PD is inhibited by NADPH. This can be overcome in the isolated perfused rat heart by increasing the oxidized glutathione and by elevating the NADP+/NADPH ratio. Besides this rapid control mechanism, there is a long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…It is, therefore, reasonable to speculate that, as a result of endothelial dysfunction, glucose is shunted through the PPP in the failing heart. Previous studies have shown that glucose is metabolized via the PPP in both healthy and diseased hearts (16,18,44,57,58). In the present study, we have shown that endothelial dysfunction and upregulated G6PD activity, in turn, leads to increased Noxcatalyzed O 2 Ϫ production in the hearts and aortas of obese, hyperglycemic, hyperinsulinemic, and hyperlipidemic rats.…”
Section: Ds-tatsupporting
confidence: 63%
See 1 more Smart Citation
“…It is, therefore, reasonable to speculate that, as a result of endothelial dysfunction, glucose is shunted through the PPP in the failing heart. Previous studies have shown that glucose is metabolized via the PPP in both healthy and diseased hearts (16,18,44,57,58). In the present study, we have shown that endothelial dysfunction and upregulated G6PD activity, in turn, leads to increased Noxcatalyzed O 2 Ϫ production in the hearts and aortas of obese, hyperglycemic, hyperinsulinemic, and hyperlipidemic rats.…”
Section: Ds-tatsupporting
confidence: 63%
“…Therefore, we and others have suggested that NADPH generated by glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme in the pentose phosphate pathway (PPP), fuels Nox and sustains O 2 Ϫ production in the heart (18,60) and vasculature (17,36). A small fraction of the total glucose in the cytosol of cardiomyocytes is oxidized to ribose by the PPP (57,58), and we recently demonstrated that overexpression of G6PD augments NADPH production, which increases O 2 Ϫ production by Nox in pacing-induced heart failure, an established model of dilated cardiomyopathy in dog (18), and in ischemic cardiomyopathy in humans (16). Likewise, several other investigators have reported carbohydrate and fatty acid metabolism to be profoundly altered in the nondiabetic failing heart (52).…”
Section: ϫ )] and The Mechanisms Underlying Omentioning
confidence: 99%
“…Alternatively, the glucose-6-phosphate (G6P) intermediate of the glycolytic pathway is capable of entering the pentose phosphate pathway in cardiomyocytes, thereby generating nicotinamide adenine dinucleotide phosphate (NADPH) and contributing to cardiomyocyte contractility. 115,130,131 It has been proposed that NADPH is crucial for the maintenance of the reduced glutathione and therefore acts protectively against the ROS-induced cell injury. 132 In good agreement with the above observation, G6P dehydrogenase (G6PD) lacking mice showed much more severe heart damage induced by the myocardial ischemia-reperfusion injury in Langendorff-perfused hearts as compared with wild-type mice.…”
Section: Protective Metabolic Pathways For Cardiomyocytesmentioning
confidence: 99%
“…76 In addition, pressure overload induces glucose 6-phosphate dehydrogenase (G6PDH), the enzyme catalyzing the flux generating step in the oxidative PPP. 77 It is therefore reasonable to assume that xylulose 5-phosphate levels increase in the hypertrophied heart due to the combined increase in glucose flux into the cardiomyocyte and increased G6PDH activity.…”
Section: Hypertrophy Diabetesmentioning
confidence: 99%